Impact Evaluation of Productive Use – An Implementation Guideline for Electrification Projects - Gunther Bensch; Jörg Peters; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
There is a consensus in the international community that rural electrification and, in particular, the productive use of electricity contributes to poverty alleviation. At the same time, efforts to evaluate the impacts of development projects have increased substantially. This paper provides a hands-on guide for designing evaluation studies regarding the impacts of productive electricity usage. Complementary to the existing literature on evaluation methods, this guide familiarizes project managers with the concrete steps that have to be undertaken to plan and implement an evaluation. The guide comprises three modules based on enterprise surveys and on anecdotal case studies. For each module, the implementation is described on a step-by-step basis including conceptual issues as well as logistics and methodological questions.
Keywords: O22; 330; Development effectiveness; productive electricity use; survey design; monitoring and evaluation